Dis/order as a New Version of the Theatre of the Absurd: Arthur Adamov's Professor Taranne as an Example - حرفوش, محمد; إبراهيم, أسامة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Western culture was redefined in the light of the calamity of World War II and its atrocities. A sense of senselessness spread out, and meaninglessness possessed meaning – it was an era of chaos, or was it really like that? The consequential European civilization of World War II is more plausibly seen as a synthesis of the antecedents and the aftermath. Europe, at that era, was actually looking back in philosophical curiosity and not in 'anger.' This philosophical attitude led to reevaluations of the relationship between system and chaos on all academic levels, especially in the theatre. A new dramatic genre originated from these sources and delved deep in analyzing their relations, i.e. the Theatre of the Absurd. Such an argument is actually the focus of the current paper, and it is fulfilled through analyzing a sample play entitled Professor Taranne Arthur Adamov.